Contralateral regional recurrence after elective unilateral neck irradiation in oropharyngeal carcinoma: A literature-based critical review. (September 2017) - Al-Mamgani, Abrahim; van Werkhoven, Erik; Navran, Arash; Karakullukcu, Baris; Hamming-Vrieze, Olga; Machiels, Melanie; van der Velden, Lilly-Ann; Vogel, Wouter V.; Klop, W. Martin
Highlights: There is long-standing convention to irradiate almost all oropharyngeal cancer (OPC) bilaterally. Contralateral regional failure (cRF) after unilateral RT of OPC is 2.4% Involvement of the midline is the most significant prognosticator for cRF after unilateral RT. Bilateral RT means an overtreatment in a substantial proportion of patients with lateralized OPC. These results call for trials to expand the indications for unilateral RT in selected groups of OPC. Abstract: Background: The head and neck region has rich regional lymphatic network, with a theoretical risk on contralateral metastasis from oropharyngeal cancer (OPC). There is a long-standing convention to irradiate the great majority of these tumors electively to both sides of the neck to reduce the risk of contralateral regional failure (cRF), but this can induce significant toxicity. We aimed to identify patient groups where elective contralateral irradiation may safely be omitted. Methods: PubMed and EMBASE were searched for original full-text articles in English with a combination of search terms related to the end points: cRF in OPC primarily treated by radiotherapy only to the ipsilateral neck and identifying predictive factors for increased incidence of cRF. The data from the identified studies were pooled, the incidence of cRF was calculated and the correlation with different predictive factors was investigated. Results: Eleven full-text articles met the inclusion criteria. In these studies, 1116 patients were treated to the ipsilateral neck alone. The mean incidence of cRF was 2.42% (range 0–5.9%, 95% CI 1.6–3.5%). The incidence of cRF correlated only with T-stage (p = 0.008), and involvement of midline (p = 0.001). However, the significant correlation with T-stage can be explained by the very low incidence of cRF among T1 (0.77%), and disappeared when the incidence of cRF was compared between T2, T3, and T4 (p = 0.344). Conclusion: The incidence of cRF in patients with OPC is very low, with involvement of midline providing the most significant prognosticator. These results call for trials on unilateral elective irradiation in selected groups.